THE IMPACT OF OBESITY ON CARDIOVASCULAR RISK. REVIEW OF THE LITERATURE - Ewa Wieczorkiewicz; Anastasiia Holoborodko; Eliza Garbacz; Patrycja Stępińska; Agnieszka Pocheć; Bartosz Lautenbach; Dariusz Nędza; Klaudia Wojciech; Anhelina Loputs; Wiktoria Błaszczyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Obesity is a global health problem due to its increasing prevalence over the past several decades. It is strongly associated with an elevated risk of cardiovascular diseases, both directly through metabolic mechanisms affecting the circulatory system and indirectly through traditional risk factors such as hypertension, dyslipidemia, and type 2 diabetes.Aim: This review discusses the pathological changes occurring in the cardiovascular system under the influence of obesity. It presents the mechanisms linking obesity with selected cardiovascular diseases and outlines the role of physical activity in obesity.Methods: The review was conducted using the PubMed, Web of Science and Google Scholar databases, limited to full-text, open-access publications from the years 2013–2025.Results: As body weight increases, the risk of cardiovascular diseases such as heart failure, hypertension, and arrhythmias also rises. Weight reduction helps lower the risk of developing these disorders. Combined aerobic and resistance training (CART), as well as High-Intensity Interval Training (HIIT), has a beneficial effect on well-being and the condition of the cardiovascular system.Conclusion: Obesity and the metabolic disturbances it causes are strongly associated with an increased risk of cardiovascular diseases. Obesity is not only a co-existing factor but also an independent risk factor for cardiovascular conditions. Effective intervention requires an individual approach.